PENDEKATAN PEMBELAJARAN TEMATIK DI SEKOLAH DASAR DALAM KURIKULUM MERDEKA - Selvi (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the implementation of the thematic learning approach in elementary schools within the Merdeka Curriculum. The Merdeka Curriculum emphasizes student-centered learning, flexibility in teaching strategies, and the development of competencies through meaningful learning experiences. The thematic learning approach is considered relevant for elementary school students because it integrates several subjects into a unified theme that is closely related to students’ daily lives. This research employs a qualitative approach using the library research method. Data were collected through the analysis of various sources such as books, research articles, scientific journals, and educational policy documents related to thematic learning and the Merdeka Curriculum. The data were analyzed through several stages including data reduction, classification, interpretation, and synthesis of relevant theories. The results of the study indicate that thematic learning supports the implementation of the Merdeka Curriculum because it promotes meaningful learning, improves students’ critical thinking skills, encourages collaboration, and strengthens character education through the integration of the Pancasila Student Profile. Thematic learning also helps teachers integrate different subjects in a more contextual and engaging way.